Waqf-linked unit trust fund: recent development within the Malaysian Islamic capital market framework - Sulaiman, Syahnaz; Hasan, Aznan (2021)
The historical evidence has shown the tremendous role of waqf institutions in the development and advancement of the Muslims. Today, waqf contributes to many spheres of life, including the mainstream economic development with the right structure and strategy. With the advancement of Islamic finance, the waqf concept has been structured to be linked with various financial products, including Shariah compliant investment instruments, such as unit trust. The aim of this paper is to highlight the recent development in the landscape of the Islamic capital market. This is in relation to the launching of the new framework aimed at facilitating the offering of Islamic funds that include the waqf features. The current study employed a qualitative research approach, which was designed through the use of document analysis of policy documents, journal articles, books, and online resources. In the last section, the paper concludes that the waqf-linked unit trust, which embraces a strong governance and robust investment framework can contribute to a sustainable development of the Islamic community’s socio-economy. In tandem with Industrial Revolution 4.0, waqf managers are encouraged to fully embrace the digital agenda in enabling a digitalized ecosystem and fintech inclusion in managing waqf funds to enhance the effectiveness of good governance and integrity in the waqf sector.